Q: 2x plus 3x equals

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

3x+5 = 2x+13 3x-2x = 13-5 x = 8

3x + 5x = 2x + 28x = 2x + 26x = 2x = (2/6) = 1/3

3x + 2x = 40 5x = 40 x = 8

If 3x + 3 = 2x + 6 then 3x - 2x = 6 - 3 x = 3

-3x + 2x = 6Let's abbreviate left part by cancellation:-x = 6The answer will be:x = -6

Related questions

3x+5 = 2x+13 3x-2x = 13-5 x = 8

3x + 8 = 2x +28 3x - 2x = 28 - 8 x=20

3x+56 = 2x+4 3x-2x = 4-56 x = -52

3x

-3x + (-18) = 2x + 7 +18 +18 -3x = 2x +25 -2x -2x -5x = 25 ----- ----- -5 -5 x=-5 *------- equals a division line

3x - 3 = 2x + 6 3x = 2x + 9 x = 9

2x + 2 = 3x - 57 = x

3x + 5x = 2x + 28x = 2x + 26x = 2x = (2/6) = 1/3

2x+3 = 3x+5 2x-3x = 5-3 -x = 2 x = -2

3x - 12 = -2x + 235x = 35 so x = 7

3x + 2x = 40 5x = 40 x = 8

2x+5=3x+1 -x=-4 x=4